Analysis and simulation of 12 pulse rectifier circuits / Nurul Akmal Mohamad Nor - Mohamad Nor, Nurul Akmal (2010)
The title of this project is Analysis and Simulation of 12 Pulse Diode Rectifier Circuit. It is basically deals with 12 pulse diode rectifier systems employing autotransformer connection for aerospace applications. The autotransformer connection with reduced kVA capacities are presented for harmonic current reduction in power diode rectifier-type utility interface systems and also reducing in kVA rating compared to the convectional 12 pulse converter.